Rainforest Relations : Gender & Resource Use by the Mende of Gola, Sierra Leone - Leach, Melissa (International African Library : IAL, 2022)
With environmental change and conservation in West Africa's tropical rainforests becoming topics of increasing political and academic interest, this book brings a fresh set of perspectives to the debate - those of the forest dwellers themselves. Based on her detailed field research in the Mende communities around Gola North Forest reserve, and surveying the recent debates and literature concerning forest conservations and current analytical approaches to gender and the environment, Melissa Leach examines the importance of rainforest resources to the local economy and social relations and shows that neither an understanding of forest use and change, nor adequate conservation policies can be achieved without a concern for gender.